2017
DOI: 10.1038/ncomms13920
|View full text |Cite
|
Sign up to set email alerts
|

Updating temporal expectancy of an aversive event engages striatal plasticity under amygdala control

Abstract: Pavlovian aversive conditioning requires learning of the association between a conditioned stimulus (CS) and an unconditioned, aversive stimulus (US) but also involves encoding the time interval between the two stimuli. The neurobiological bases of this time interval learning are unknown. Here, we show that in rats, the dorsal striatum and basal amygdala belong to a common functional network underlying temporal expectancy and learning of a CS–US interval. Importantly, changes in coherence between striatum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 66 publications
(90 reference statements)
6
49
0
Order By: Relevance
“…We tested DAR models on three different datasets, with invasive recordings in humans and rodents: 1. A rodent local field potential (LFP) recording in the dorso-medial striatum from [Dallérac et al, 2017](supplementary figure 2), (1800 seconds down-sampled at 333 Hz) 2. A rodent LFP recording in the hippocampus from [Khodagholy et al, 2015] collected during rapid eye movement (REM) sleep (100 seconds down-sampled at 625 Hz) 3.…”
Section: Empirical Datasetsmentioning
confidence: 99%
“…We tested DAR models on three different datasets, with invasive recordings in humans and rodents: 1. A rodent local field potential (LFP) recording in the dorso-medial striatum from [Dallérac et al, 2017](supplementary figure 2), (1800 seconds down-sampled at 333 Hz) 2. A rodent LFP recording in the hippocampus from [Khodagholy et al, 2015] collected during rapid eye movement (REM) sleep (100 seconds down-sampled at 625 Hz) 3.…”
Section: Empirical Datasetsmentioning
confidence: 99%
“…One task that provides an ideal window into behavioral flexibility is interval timing, which requires participants to estimate an interval of several seconds via a motor response. Across species, interval timing requires the prefrontal cortex and striatum (Coull et al, 2011; Dallérac et al, 2017; Emmons et al, 2017, 2016; Matell and Meck, 2004; Merchant and de Lafuente, 2014). Work from our group and others has shown that both prefrontal and striatal neurons encode temporal information via ‘time-related ramping’ activity—or monotonic changes in firing rate over a temporal interval (Bakhurin et al, 2017; Donnelly et al, 2015; Emmons et al, 2017; Kim et al, 2018; Narayanan, 2016; Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is closely related to cognitive mechanisms such as attention, high-level visual processing and motor control. The first signal (LFPcortical) is recorded in the rat cortex [17], while the second one (LFP-striatal) is recorded in the rat striatum [41]. Figure 8 shows samples from these two data sets.…”
Section: Local Field Potential Datamentioning
confidence: 99%